NANDONG INUMAN RANTAU KUANTAN KAJIAN GENRE SASTRA PUISI DAN KEARIFAN LOKAL - Novriadi Oktavian; Syafrial Syafrial; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Malay nation is a nation that is cultured, dynamic and open. Malay nation can develop in various ways. One of them is by way of Malay wisdom thinking that basically often takes the example of natural example. With openness, culture, Malay society, with strict judgment and judgment, is not in accordance with external culture, which is appropriate and harmonious with the values, cultural principles. Various methods have been applied by Malay people in Rantau Kuantan in order to enrich their local wisdom, one of which is through keratif literary or continuous processes in which local wisdom can be used in several oral publications that exist and develop in the Inuman Rantau Kuantan community. One process for literature or sustainability is nandong, or humming. Inuman, Rantau Kuantan which is part of the Malay cultural region itself has various types of nandong which are scattered and have become inherent in the daily lives of their people. This research includes child bedtime songs whose texts consist of mantra, gurindam, syair, pantun, seloka, and thimbles or other traditional research.Keywords: nandong, poetry literary genre, local wisdom.